Intergenerational social mobility and health in Brazil: analyzing the "Social Dimensions of Inequalilies Survey (PDSD)," 2008 - Flor, Luisa Sorio; Laguardia, Josué; Campos, Monica Rodrigues (Ciência & saude coletiva, 2014)
Although most studies consider health to be the result of social and economic insertion of the individuals, health may be considered a determining factor of the social opportunities achieved, especially with respect to chances of social mobility. The scope of this article is to understand the magnitude of the concurrent associations that sociodemographic, health and quality of life conditions (SF-36) exercise on chances of intergenerational social mobility on a probability sample of Brazilian homes in 2008. Social mobility was determined by the transition between occupational groups, which were defined using the Ganzeboom scale. Sociodemographic, health and quality of life features were associated with upward social mobility through logistic regression. A high level of schooling was the main determinant of chances of intergenerational social mobility. Women and youngsters ascended more intergenerationally. A positive association was observed between self assessment of health, physical health scores and upward mobility. Social mobility has become established as a multideterminate event. Physical health and perceived health were capable of influencing social transitions.